Pengaruh Intensitas Penggunaan Aplikasi Digital Qur’an terhadap Kemampuan Membaca Al-Qur’an Siswa Kelas IX di SMP Negeri 4 Manyabar - Mutiara Sari; Syamsiah Depalina Siregar (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
This study aims to measure the effect of the intensity of use of digital Al-Qur'an applications on the ability to read the Al-Qur'an of ninth-grade students at SMP Negeri 4 Manyabar. The study used a quantitative approach with an ex-post facto method, namely looking at the relationship between the intensity of use of digital Al-Qur'an applications (independent variable) and the score of the ability to read the Al-Qur'an (dependent variable) without direct treatment manipulation of the respondents. The sample was taken by purposive sampling from 80 ninth-grade students who actively use the Al-Qur'an application in daily learning. The research instruments were a questionnaire on the intensity of use of the application and a test of the ability to read the Al-Qur'an assessed by two competent assessors. Data were analyzed by simple linear regression using SPSS software. The results showed a positive and significant effect between the intensity of use of digital Al-Qur'an applications on students' ability to read the Al-Qur'an (p < 0.05), so that the intensity of use of digital Al-Qur'an applications contributes to improving the ability to read the Al-Qur'an. This finding is in line with various previous studies showing that digital Al-Qur'an applications can improve skills and motivation to read the holy book among school and university students.